PENCEMARAN LINGKUNGAN DAN APLIKASI KEBIJAKAN PENGENDALIANNYA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: This paper demonstrates that polluters not only refer to a company or individual but also includes government and society. In economic perspective, the impacts of economic activities on environment are considered externalities (external costs). In order to develop an environmentally friendly economic system, every economic activity needs to internalize the external costs as one of the components of production costs. In this regard, environmental economics plays an important role in valuing such externalities. Various policy instruments are also discussed in this paper in order to support sustainable environmental development. It is concluded that with no market distortion, market-based mechanism instrument is considered effective in protecting environment. If market distortion exists, however, regulation-based instrument is considered more effective.